"Red Data Book of Ukraine. Vegetable Kingdom" Afterword - Didukh, Yakiv (Biodiversity: Research and Conservation, 2011)
The results of the third edition of the Red Data Book of Ukraine (2009) are summed up. This edition includes 826 species (611 vascular plants, 46 bryophytes, 60 algae, 52 lichens, 57 mosses). The approaches to species selection and category comparing assessment, which are accepted by Ukraine and IUCN, are highlighted as well as species distribution according to phytoceonological and political regions. Approaches to the selection of species for inclusion in the lists of the Red Data Books of Ukraine and Poland are analyzed.